The configuration of the Spanish public sphere : from the Enlightenment to the indignados - Jiménez Torres, David, 1986-; Villamediana González, Leticia (Studies in Latin American and Spanish history, 2019)
"Since the explosion of the indignados movement beginning in 2011, there has been a renewed interest in the concept of the 'public sphere' in a Spanish context: how it relates to society and to political power, and how it has evolved over the centuries. The Configuration of the Spanish Public Sphere brings together contributions from leading scholars in Hispanic studies, across a wide range of disciplines, to investigate various aspects of these processes, offering a long-term, panoramic view that touches on one of the most urgent issues for contemporary European societies"--